High burden of previously undiagnosed HIV infections and gaps in HIV care cascade for conflict-affected female sex workers in northern Uganda. (March 2019) - Goldenberg, Shira M; Muzaaya, Godfrey; Akello, Monica; Braschel, Melissa; Birungi, Josephine; Shannon, Kate
Given the disproportionate HIV burden faced by female sex workers FSWs and limited data regarding their engagement in the HIV cascade of care in conflict-affected settings, we characterized the cascade of care and examined associations with new HIV diagnoses and antiretroviral therapy (ART) use in a community-based cohort of FSWs in conflict-affected Northern Uganda. Data were collected via FSW/peer-led time-location sampling and outreach, interview-administered questionnaires, and voluntary HIV testing. Of 400 FSWs, 33.5% were living with HIV, of whom 33.6% were new/previously undiagnosed infections and 32.8% were on ART. Unstable housing and heavy alcohol/drug use were independently associated with increased odds of new HIV diagnoses, whereas exposure to condom demonstrations and number of lifetime pregnancies were negatively associated. In subanalysis among known HIV-positive women, age and time since diagnosis were associated with ART use, whereas sexually transmitted infections were negatively associated. Findings suggest the need for FSW-tailored, peer-based, and integrated HIV and sexual and reproductive health programs to address gaps in HIV testing and treatment for FSWs in conflict-affected communities.